HUBUNGAN PENERAPAN ABSENSI BERBASIS SISTEM BARCODE DALAM MENINGKATKAN KEDISIPLINAN SISWA DI SDN KOTABATU 01 - Siti Nurjanah; Rika Rostiany; Tia Putri Pratiwi (Sekolah Tinggi Ilmu Tarbiyah Insan Kamil Bogor, 2025)
This study aims to examine the correlation between the implementation of a barcode-based attendance system and the improvement of student discipline at SDN Kotabatu 01. A quantitative research method was employed, utilizing both descriptive and inferential statistical approaches. Data collection was conducted through direct observation, questionnaires, and documentation. The research population comprised all 586 students enrolled at SDN Kotabatu 01, with a sample of 85 fourth-grade students selected through probability sampling using the cluster sampling technique. The findings revealed that student discipline levels were distributed across two main categories: moderate (31%, or 26 students) and high (69%, or 59 students). Regarding the implementation of the barcode-based attendance system, 58 students (68%) were categorized as moderate, while 27 students (32%) fell into the high category.The linearity test indicated that the calculated F-value (1.114) was lower than the critical F-value (3.96), suggesting a linear relationship between the independent variable (barcode-based attendance implementation) and the dependent variable (student discipline). The resulting linear regression equation, Ŷ = 95.408 + 0.332X, implies that for every one-unit increase in the implementation of the barcode attendance system, the student discipline score increases by 0.332 points. Furthermore, the coefficient of determination (R²) was found to be 0.083, indicating that the barcode-based attendance system contributes 8.3% to the variation in student discipline, while the remaining 91.7% is attributable to other unexamined factors.